2009
DOI: 10.1051/radiopro/20095028
|View full text |Cite
|
Sign up to set email alerts
|

Radioadaptation of rodents in the zone of local radioactive contamination (Kyshtim Accident, Russia): 50 years on

Abstract: Abstract.Results of radioecological investigations of rodents having different ecological specializationwood and field mice, northern red-backed voles and mole-voles to acute (laboratory experiment) and chronic (long-term inhabiting the East Ural Radioactive Trace -EURT) irradiation are summarized. These species are greatly distinguished by a way of life, a migratory activity, an average life span etc. Numerous immunological, hematological and cytogenetical disturbances were found in more radioresistant wood a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…However, the possibility of radioadaptation in a series of generations that developed due to ecophysiological features (subterranean borrowing way of life, quite low migratory activity) and isolation of settlement in the EURT zone (since 1957) was shown in mole-voles (Ellobius talpinus) [13,14]. But mice and voles form a flowing population and slip off the prolonged influence of a damaging factor, this circumstance prevents the development of radioadaptation [3]. Multigenerational effects induced by chronic external and internal irradiation by 137 Cs (direct effects, transgeneration transmission of radiation-induced damages, radioadaptive effects) have been observed in natural bank vole (Clethrionomys glareolus) population inhabiting in the Chernobyl zone [15].…”
Section: Accumulation Of 90 Srmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the possibility of radioadaptation in a series of generations that developed due to ecophysiological features (subterranean borrowing way of life, quite low migratory activity) and isolation of settlement in the EURT zone (since 1957) was shown in mole-voles (Ellobius talpinus) [13,14]. But mice and voles form a flowing population and slip off the prolonged influence of a damaging factor, this circumstance prevents the development of radioadaptation [3]. Multigenerational effects induced by chronic external and internal irradiation by 137 Cs (direct effects, transgeneration transmission of radiation-induced damages, radioadaptive effects) have been observed in natural bank vole (Clethrionomys glareolus) population inhabiting in the Chernobyl zone [15].…”
Section: Accumulation Of 90 Srmentioning
confidence: 99%
“…This approach supposes to divide natural population into groups of individuals with the same functional status, i. e. with the uniform patterns of growth and/or maturation rate as well as whether they participate in reproduction (scheme of two alternative pathways of mouse-like rodents' ontogenetic development presented early [3]. Individuals of different types of ontogeny (functional status) manifest significantly diverse radioresistance [5].…”
Section: Functional-ontogeny Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…These animals have demonstrated the activation of immune system, completeness of immune response to infection. Effects such as increase in the frequency of aberrant cells, pathological changes and suppression of both immune and hematopoietic systems were not seen [10,12,17,18]. Lyubashevskiy et al [18] have concluded that EURT mole vole have developed perfect adaptation to the surrounding radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of doses and effects of irradiation on plants are presented in [3,4]. Among other animals, the murine rodents are the most studied [5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%